Cognitive impairment and morphological changes after radiation therapy in brain tumors: A review. Issue 2 (August 2018) - Jacob, Julian; Durand, Thomas; Feuvret, Loïc; Mazeron, Jean-Jacques; Delattre, Jean-Yves; Hoang-Xuan, Khê; Psimaras, Dimitri; Douzane, Hassen; Ribeiro, Monica; Capelle, Laurent; Carpentier, Alexandre; Ricard, Damien; et al.
Abstract: Life expectancy of patients treated for brain tumors has lengthened due to the therapeutic improvements. Cognitive impairment has been described following brain radiotherapy, but the mechanisms leading to this adverse event remain mostly unknown. Technical evolutions aim at enhancing the therapeutic ratio. Sparing of the healthy tissues has been improved using various approaches; however, few dose constraints have been established regarding brain structures associated with cognitive functions. The aims of this literature review are to report the main brain areas involved in cognitive adverse effects induced by radiotherapy as described in literature, to better understand brain radiosensitivity and to describe potential future improvements.